Distribution and controlling factors of microplastics in surface sediments of typical deep-sea geomorphological units in the northern South China Sea - Zhang, Xiaodong; Liu, Zhifei; Zhao, Yulong; Ma, Pengfei; Colin, Christophe; Lin, Andrew Tien-Shun (Frontiers in Marine Science, 2022)
Marine microplastics are widely distributed in deep-sea sedimentary environments and are altering sediment compositions and ecological conditions on the seafloor. However, the relation between the distribution of microplastics in deep-sea sediments and the sedimentary dynamic conditions is poorly understood. In this study, we collected surface sediments from some typical geomorphological units (sand dune, sediment drift, and submarine canyon channel/levee) in the northern South China Sea to study composition and distribution of the deep-sea microplastics and their controlling factors. The results show that the microplastic abundance in surface sediments ranges from 19 to 347 p·kg–1, and the identified microplastics consist of 10 types, including dominant polycarbonate (29%), polyethylene (27%), polyester fiber (16%), polyvinyl chloride (13%), and polypropylene (7%), and minor polyethylene terephthalate resin, acrylonitrile-butadiene-styrene, epoxy resin, hydrocarbon resin, and acrylic. The source analysis shows that the deep-sea microplastics may be influenced by riverine inputs from Taiwan and South China. In addition, the microplastic spatial distribution shows that the sand dune and canyon channel contain the highest abundances (136–347 p·kg–1) and more types (4–6 types) of microplastics, which are dominated by relatively high-density polycarbonate or polyvinyl chloride. The canyon levee contains the lowest abundances (19–132 p·kg–1) and less types (1–3 types) of microplastics, which are dominated by relatively low-density polyester fiber or polyethylene. Nevertheless, the microplastic composition of the sediment drift is between those of the canyon channel and the canyon levee. The abundance and polymer type (density) of microplastics all increase with the increased mean grain size of detrital sediments, which represents the progressively enhanced intensity of sedimentary dynamic conditions. We therefore infer that the sedimentary dynamic conditions control the composition and distribution of microplastics in the deep-sea sediments. This study highlights that some deep-sea environments with stronger sedimentary dynamic conditions may accumulate more microplastics, which is of great significance for evaluating the storage and ecological damage of deep-sea microplastics.